2019
DOI: 10.1121/1.5084042
|View full text |Cite
|
Sign up to set email alerts
|

An analytic physically motivated model of the mammalian cochlea

Abstract: We develop an analytic model of the mammalian cochlea. We use a mixed physicalphenomenological approach by utilizing existing work on the physics of classical boxrepresentations of the cochlea, and behavior of recent data-derived wavenumber estimates. Spatial variation is incorporated through a single independent variable that combines space and frequency. We arrive at closed-form expressions for the organ of Corti velocity, its impedance, the pressure difference across the organ of Corti, and its wavenumber. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…In the expression, p = ib p − A p and p = −ib p − A p . The model constants A p , B u , b p take on real positive values, and we have shown that they vary slowly along the length of the cochlea [12] (recall that for many of the diverse set of applications in section I, it is desirable for the filters to mimic signal processing by the auditory system). If the filters are sharply tuned, A 2 p + b 2 p ≈ b 2 p , and if the peak frequency occurs at CF(x) (i.e.…”
Section: Transfer Functionsmentioning
confidence: 90%
See 4 more Smart Citations
“…In the expression, p = ib p − A p and p = −ib p − A p . The model constants A p , B u , b p take on real positive values, and we have shown that they vary slowly along the length of the cochlea [12] (recall that for many of the diverse set of applications in section I, it is desirable for the filters to mimic signal processing by the auditory system). If the filters are sharply tuned, A 2 p + b 2 p ≈ b 2 p , and if the peak frequency occurs at CF(x) (i.e.…”
Section: Transfer Functionsmentioning
confidence: 90%
“…1) Transfer functions: GAFs were derived in the frequency domain based on a physical-phenomenological model of the cochlea operating at low stimulus levels and is tightly linked to frequency domain mechanistic variables of the associated cochlear model that are useful for studying how the cochlea functions [12]. Here we extend our study of the transfer functions to rational exponent GAFs.…”
Section: A Representationsmentioning
confidence: 98%
See 3 more Smart Citations